Intervenções artística e transtornos psíquicos: possibilidades de diálogos - Cavalcanti, Ana Elizabeth Lisboa Nogueira (2013)
The art has been implicated as a possible therapeutic tool in the treatment of patients suffering from mental disorders in that it can trigger emotions and feelings repressed in the conscious and in the unconscious. An instrument that can arouse subjectivities. This thesis work was developed through an Artistic Residency with adult patients of both sexes, suffering from mental disorders, internee in the Ulysses Pernambucano Hospital (HUP) and attending the Therapeutic Activities Center (CAT), whose goal is to host patients and stimulate the various artistic languages. To this end, we intend, through the artistic residency, identify the use of art as a clinical device of subjectivities expression for people with mental disorders, with a view to proposing this treatment modality for these patients. The method used was the cartographic, suitable for the fieldwork that aims study subjectivities. It has also produced a Field Journal in order to register the step-by-step of the Artistic Residency, from first to last moment. Photographs and recordings were made and, in the latter case, transcribed its contents to subsidize the research, and its informations included in the Field Journal. The Artistic Residency consisted of painting and drawing sessions, three times a week, from September 2011 to May 2012, with entirely voluntary participation of patients. Two roving easels were built, initially placed in the CAT room, being transferred later to the courtyard of the institution. At first shy and curious, patients were coming up slowly, painted and sketched the reasons they wanted, using paints, brushes, pencils, wood, paper and fabrics. Concomitant with the realization of artistic experiences, some danced, sang, complained, told stories, wrote, cursed, finally, at long last, they expressed the most different ways of being and living in that place; repressed emotions that were being unlocked. A rich artistic and interpersonal interaction was formed, strong bonds of friendship, trust, motivation, companionship, love. While they painted, patients talk about their anxieties, sorrows, life experiences, facts and events significant to them, giving contour to the word by art and art by the word of their different "states of being". The artwork resulted in a total of 14 screens painted with acrylic paint, size 2,0 x 1,60 , addressing various reasons; a wall installation made of painted wood was done, games in wood, several drawings on paper were performed. The results indicate a significant change in mental status of patients, interaction with the art/education team, creating bonds of friendship and mutual aid. It was evident a substantial improvement in attitudes, motivation and behavior of many patients, showing that art can be an important tool as an adjunct in the treatment of these patients. Moreover, the lived experience abled broaden perspectives on institutional dynamics, from the perspective of the difficulties faced in continuing to pursue its mission, and the necessary changes toward a psychiatric reform nonexclusive, facing the dignity of every human being, regardless of their state of being.